Angiosomes of medial cord of brachial plexus - Suseelamma, D.; Deepthi, S.; Chaitanya, K. Krishna; Sharada, H. R. (International Journal of Research in Medical Sciences, 2017)
This anatomical study analyzed the neurovascular relationship of the brachial plexus. Ten formalized specimens of brachial plexuses were examined after injection of lead oxide in to the subclavian artery. The vascular, anatomical features of the brachial plexus were documented .The specimens were analyzed by dissection method, subjected for microscopic study. The vascular supply was markedly rich, often with true anastomotic channels found within the nerves. There was much variation in supply, depending on the branching pattern of subclavian artery.